2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720597
|View full text |Cite
|
Sign up to set email alerts
|

Integrated teaching of programming foundations and software testing

Abstract: -The importance of software testing is widely recognized, but usually only a small portion of the Computer Science (CS) curriculum is allocated for teaching it. Some experiences have suggested that the teaching of software testing should begin as early as possible so an adequate culture of testing could be created. One way to achieve this is addressing testing practices in conjunction with programming concepts in introductory CS courses. In this paper we explore such idea, working on the integration between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
11
0
9
Order By: Relevance
“…The idea is to promote the introduction of testing practices together with programming foundations. For instance, PROGTEST [43,44] assesses students' assignments by: (i) checking the correctness of the student's program, comparing its output with the output of a model program; (ii) executing the student's test suite against his/her program to assess how well he/she tested his/her program; and (iii) executing the student's test suite against the model program to identify problems in the test cases designed by the student. As discussed before, many tools have specialties that aim to support specific goals such as the handling of programming exams and the introduction of testing activities in programming courses.…”
Section: Legendmentioning
confidence: 99%
“…The idea is to promote the introduction of testing practices together with programming foundations. For instance, PROGTEST [43,44] assesses students' assignments by: (i) checking the correctness of the student's program, comparing its output with the output of a model program; (ii) executing the student's test suite against his/her program to assess how well he/she tested his/her program; and (iii) executing the student's test suite against the model program to identify problems in the test cases designed by the student. As discussed before, many tools have specialties that aim to support specific goals such as the handling of programming exams and the introduction of testing activities in programming courses.…”
Section: Legendmentioning
confidence: 99%
“…This is done with the perspective of how well the courses support the progressive development of both students' knowledge of software testing and their ability to test software systems. Barbosa et al (2008) suggested that teaching of software testing should begin as early as possible so that an adequate culture of testing can be created. They proposed PROTEST -a Web-based environment for the submission and automatic evaluation of practical programming assignments based on testing activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In higher education learning, students in computer programming courses usually find the subject as difficult and complex [1], [2]. Among the main problems in programming learning involve difficulty to understand variety of technical topics such as variables and functions and further to apply the concepts to execute computer program [3], [4]. The problems usually create other issues related to lack of motivation and engagement in class [5], [6].…”
Section: Introductionmentioning
confidence: 99%